+0  
 
0
89
1
avatar+4 

What is (f•g)( x)?

f(x)=x^3-4x+2 

g(x)=x^2+2 

(f•g)(x)= 

Gothbaby  Jun 13, 2018
 #1
avatar+84 
0

(f•g)(x) --> f(g(x))
Basically, where there is an x, replace it with g(x), in this case x2+2

f(x)=x3-4x+2

f(x2+2)=(x2+2)3-4(x2+2)+2
           =x6+6x4+12x2+8-4x2-8+2
           =x6+6x4+8x2+2

ChowMein  Jun 13, 2018

10 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.